Study on Controlled Slow Release Action of Nitrendipine/MCM-41 Drug Loading System - Li, Jing-Mei; Yu, Hui; Li, Xiao-Dong; Zhai, Qing-Zhou; Tian, Jian (Asian Journal of Chemistry, 2011)
In the study, MCM-41 molecular sieves were modified with trimethylchlorosilane before calcination. Nitrendipine was doped inside the pores of the modified MCM-41 via liquid-phase grafting method and the prepared drugs kept the structures of mesoporous pore. The drug release process from the matrix into a simulated body fluid (SBF) solution has been studied. The results showed that the process was divided into four stages. It was observed that the samples showed a sharp initial release burst after 2 h for unmodified nm-MCM-41 as carrier (MN) sample and 1 h for modified nm-MCM-41 as carrier (MMN) sample. By the way of modified before calcination, the drug was doped inside the pores of molecular sieve mainly and made the release become slowly, respectively. For the unmodified MCM-41 sample, the release effect of nitrendipine was 51.4 % at 5 h and was 99.6 % at 30 h. For the modified MCM-41 sample, the release effect of nitrendipine was 51.4 % at 7 h and was 99.7 % at 34 h.